Penguatan Peran Perempuan dalam Mewujudkan Pariwisata Berkelanjutan dan Inklusif di Desa Jambu Baru Kabupaten Barito Kuala - Hamid , Ismar; Hidayah, Sri; Nugroho, Arif Rahman; Zulaikha, Siti; Liani, Sava'ah Intan; Alhadi, Syarifah Soraya; Safitri, Mahtia; Zulhidan, Muhammad Royyan (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Today's worsening climate change has a significant impact on the economic activities of the community in Jambu Baru Village, Kuripan Sub-district, Barito Kuala Regency. In general, the problems faced are also influenced by the management of economic resources that still depend on traditional methods. Almost all community economic activities have experienced a decline in income as a result of climate change. For example, from beje management, the community still relies heavily on income from the harvest, despite facing harvest uncertainty due to the uncertain season. Adaptation efforts have led to a new source of income, namely fishing tourism by utilizing beje, but is still positioned as additional income. In this case, creative economic opportunities have not been managed to support community adaptation in facing the impacts of climate change. This service program are highlighted problems: (1) The absence of creative and innovative ideas in the development of sustainable fishing tourism in Jambu Baru Village; (2) Women have not played a role in the management and development of fishing tourism in Jambu Baru Village. Problem solutions are designed using a sustainable development approach, which emphasizes the importance of climate change mitigation and adaptation in the context of peatland management. Concretely, the program implemented is strengthening the role of women in realizing sustainable and inclusive tourism. After carrying out village discussions and workshops, women's groups in Jambu Baru Village have creative and innovative ideas for the development of sustainable fishing tourism. The commitment of the women's groups to play an active role as a social base to implement these ideas was also strengthened.